Sensor network localisation based on sorted RSSI quantisation. (27th July 2006) - Li, Xiaoli; Shi, Hongchi; Shang, Yi
Range estimation is essential in many sensor network localisation algorithms. Although wireless sensor systems usually have available received signal strength indication (RSSI) readings, this information has not been effectively used in the existing localisation algorithms. In this paper, we present a novel approach to localisation of sensors in an ad hoc sensor network based on a sorted RSSI quantisation algorithm. This algorithm can improve the range estimation accuracy when distance information is not available or too erroneous. The range level used in the quantisation process can be determined by each node, using an adaptive quantisation scheme. The new algorithm can be implemented in a distributed way and achieves significant improvement over existing range-free algorithms. The performance advantage for various sensor networks is shown, with experimental results from our extensive simulation with a realistic radio model.